ANALISIS DU PONT SYSTEM DALAM MENGUKUR KINERJA KEUANGAN PERUSAHAAN (STUDI KASUS PADA PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Johanes Daniel (Seminar Nasional Ilmu Terapan, 2024)
Du Pont System analysis includes all activity ratios and profit margins on sales to show how these ratios affect profitability, and is an integrative measurement of financial performance. This research was conducted to find out how effective the company is in managing the company's financial performance. This study aims to determine the analysis of the financial performance of telecommunication companies listed on the Indonesia Stock Exchange (IDX) in 2020-2022 using the Du Pont System Analysis. PT Telekomunikasi Indonesia Tbk, PT XL Axiata Tbk, PT Indosat Tbk and PT Smartfren Telecom Tbk by using the Du Pont System Method.Data analysis method used in this research is Du Pont System Method. The variables used in this study are Total Asset Turnover, Net Profit Margin, and Return on Investment. The data used are secondary data in the form of company financial statements. The results showed that PT Telekomunikasi Indonesia Tbk has a very good financial performance where all variables are above the industry average. PT XL Axiata Tbk has a fairly good financial performance because only the Net Profit Margin variable is above the industry average. PT Indosat has a relatively good financial performance where only the Total Asset Turnover variable is above the industry average. PT Smartfren Telecom Tbk has poor financial performance because all variables are below the industry average.